2001
DOI: 10.1590/s0037-86822001000600011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos sorológicos e epidemiológicos da leishmaniose tegumentar americana canina em Maricá, Rio de Janeiro, Brasil

Abstract: Resumo Foram estudados 261 cães (134 moradias) do Município de Maricá, RJ, Brasil, visando avaliar a resposta sorológica e infecção ativa para leishmaniose tegumentar americana (LTA). Oito cães apresentaram lesões sugestivas, sendo o isolamento positivo em 3. Pelo ELISA, 24,5% (64/261) apresentaram reatividade (sensibilidade = 66% e especificidade = 76%), estando associado ao isolamento em 2 e 0,4% (1/261) pela imunofluorescência indireta (RIFI) sem associação com isolamento. Para a redução de reações inespecí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
7
1
5
Order By: Relevance
“…However, variation in the prevalence rate is very high (2.16 to 54.7%) when considering the values estimated by other authors (Pereira et al, 2008;Reis et al, 2011;Araújo et al, 2014;Carvalho et al, 2015;Leça-Júnior et al, 2015). Although IFAs are widely employed for their convenience and low cost, their use is controversial owing to low levels of detectable serum antibodies and the possibility of cross-reactions (Antunes Uchôa et al, 2001). Serological diagnosis results vary depending on the stage of infection (Heusser Júnior et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, variation in the prevalence rate is very high (2.16 to 54.7%) when considering the values estimated by other authors (Pereira et al, 2008;Reis et al, 2011;Araújo et al, 2014;Carvalho et al, 2015;Leça-Júnior et al, 2015). Although IFAs are widely employed for their convenience and low cost, their use is controversial owing to low levels of detectable serum antibodies and the possibility of cross-reactions (Antunes Uchôa et al, 2001). Serological diagnosis results vary depending on the stage of infection (Heusser Júnior et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Serological diagnosis results vary depending on the stage of infection (Heusser Júnior et al, 2010). According to Antunes Uchôa et al (2001), higher levels of specific antibodies are produced when multiple cutaneous lesions are present in the later stages of infection, and in cases with simple skin lesions and lymphatic system involvement. In addition, seroconversion may take up to 22 months; therefore, during this period, it is not possible to detect infected animals by serological methods (Solano-Gallego et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Uchôa et al (2001) suggested that serological techniques must be used in combination with other diagnostic tests, such as direct PCR-based parasitological exams or the rapid immunochromatographic test.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, quando aplicado em estudos epidemiológicos na LTA, a especificidade do ELISA pode tornar-se baixa, devido a ocorrência de reações inespecíficas 17 .…”
Section: Methodsunclassified